2015
DOI: 10.1093/jb/mvv041
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-related inhibition of pro-inflammatory responses and oxidative stress are involved in the mechanism of nonspecific low back pain relief after exercise through modulation of Toll-like receptor 4

Abstract: Low back pain is a common clinical problem that causes disability and impaired quality of life. While the reason behind low back pain was largely considered to be of musculoskeletal origin, the contribution of inflammatory cytokines and oxidative stress could never be overlooked. Exercise has been proven to be an effective approach to treat low back pain. However, the mechanism of the exercise effect on the inflammatory cytokines and oxidative stress is still largely unknown. In this study, we revealed that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…Cheng et al (2015) revealed that exercise activated SIRT1 activity, which reduced NF-κB, TLR-4, IL-1β, IL- 6, IL-8, and TNFα inflammatory activity. A murine sepsis model in C57BL/6 mice injected with LPS stimulated TLR4 and activated SIRT1 , which induced NF-κB p65 deacetylation and deactivation thus inhibiting pro-inflammatory gene expression (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al (2015) revealed that exercise activated SIRT1 activity, which reduced NF-κB, TLR-4, IL-1β, IL- 6, IL-8, and TNFα inflammatory activity. A murine sepsis model in C57BL/6 mice injected with LPS stimulated TLR4 and activated SIRT1 , which induced NF-κB p65 deacetylation and deactivation thus inhibiting pro-inflammatory gene expression (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Sirtinol also reversed the inhibitory effects of ATX on TLR4 activation and the subsequent neuroprotection. Although several studies have reported that SIRT1 could modulate the TLR4/NF-кB pathway, the authors did not analyze the exact molecular mechanisms between them (67,68). In addition, no study has reported that SIRT1 can regulate the TLR4/NF-кB pathway under physiologic and pathologic conditions (i.e., SAH).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of ST36 acupoint by BVA can decrease chronic constrictive injury of sciatic nerve-induced neuropathic pain by activation of α-adrenoceptros, but not through opioid receptors (Roh et al, 2004). Also, Tsai et al, (2015) suggested that BV injection at a certain acupoints (LI4, SI3, KI3, ST36, BL23, BL40, CB30, GB34, LR3, unilateral GV1) can enhance treatment of canine neurological dysfunction by intervertebral disk disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Chen and Lariviere (2010) considered that BV having nociceptive and anti-nociceptive effects together this is called a "double-edged sword'. Also, other descending inhibitory systems like GABA, serotonergic and/or cholinergic systems might be involved and Park et al, 2009.…”
Section: Discussionmentioning
confidence: 99%